Thành phần hóa học của cây Ngọc cẩu (Balanophora laxiflora Hemsl.) thu tại Tuyên Quang. Phần 1. Thành phần hóa học của các cặn chiết ít phân cực. - Đại, Trần Đức; Tiến, Nguyễn Quyết; Tuấn, Nguyễn Ngọc; An, Nguyễn Quảng; Thanh Nga, Trương Thị; Thủy, Trịnh Thị; Tuyết, Nguyễn Thị; Quang, Đặng Ngọc (Vietnam Journal of Chemistry, 2017)
Balanophora laxiflora Hemsley has been used in Vietnamese folk medicine for clearing away heat and toxic, neutralizing the effect of alcoholic drinks, and as a tonic for the treatment of hemorrhoids, stomachache and hemoptysis. Phytochemical investigation of the nonpolar solvent extracts of Balanophora laxiflora led to the isolation of fatty substance 1-hexacosanoylglycerol (1), daucosterol (2), methyl gallate (3), three cinnamic acid analogues:4-hydroxy-3-methoxycinnamaldehyde (4), methyl 4-hydroxy cinnamate (5), and methyl caffeate (6). Their chemical structures were confirmed by spectroscopic methods including IR, MS, 1D, 2D NMR and compared to previous reported spectral data values. Keywords. Balanophora laxiflora, derivatives of cinnamic acid, lignan, methyl gallate, daucosterol.